2008
DOI: 10.1002/jnr.21850
|View full text |Cite
|
Sign up to set email alerts
|

The amino terminus of tau inhibits kinesin‐dependent axonal transport: Implications for filament toxicity

Abstract: The neuropathology of Alzheimer's disease (AD) and other tauopathies is characterized by filamentous deposits of the microtubule-associated protein tau, but the relationship between tau polymerization and neurotoxicity is unknown. Here, we examined effects of filamentous tau on fast axonal transport (FAT) using isolated squid axoplasm. Monomeric and filamentous forms of recombinant human tau were perfused in axoplasm, and their effects on kinesin- and dynein-dependent FAT rates were evaluated by video microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
253
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(276 citation statements)
references
References 61 publications
18
253
0
1
Order By: Relevance
“…The functional consequence of GSK3-mediated phosphorylation of KLC was release of kinesin-1 from its vesicle cargoes (22,23,40). Consistent with this observation, the amount of kinesin-1 on axoplasmic vesicles was substantially reduced relative to controls with both oA␤ and CK2 perfused axoplasms (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The functional consequence of GSK3-mediated phosphorylation of KLC was release of kinesin-1 from its vesicle cargoes (22,23,40). Consistent with this observation, the amount of kinesin-1 on axoplasmic vesicles was substantially reduced relative to controls with both oA␤ and CK2 perfused axoplasms (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…3B). Previous studies with GSK3 showed that the 63-90 epitope was also sensitive to GSK3 activity (22,23,40). Significantly, CK2 was a priming kinase for GSK3 modification of KLC and GSK3 did not phosphorylate KLC without a priming phosphorylation (22).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…34 The aggregation of tau can also inhibit anterograde axonal transport. 35 Abnormalities in axonal processes appear as tau positive NTs, which might occur before tau accumulation within the soma of the neuron. 28,36 The onset of axonal/dendritic pathology within the CBF and its relation to cholinergic neuronal NFT development during the progression of AD remains unresolved.…”
mentioning
confidence: 99%